2021
DOI: 10.14569/ijacsa.2021.0120149
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Methodologies for the Development of Embedded Systems

Abstract: Embedded systems encompass software and hardware components developed in parallel. These systems have been the focus of interest for many scholars who emphasized development issues related to embedded systems. Moreover, they proposed different approaches for facilitating the development process. The aim of this work is to identify desirable characteristics of existing development methodologies, which provide a good foundation for development of new methodologies. For that purpose, systematic mapping methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…The studies [Xie et al 2012, Rong et al 2014, Blaškovic et al 2021] conducted a systematic review of the application of agile methods to embedded software development. They identified that XP and Scrum are the methods more used by these projects.…”
Section: Ronkainem and Abrahamssonmentioning
confidence: 99%
“…The studies [Xie et al 2012, Rong et al 2014, Blaškovic et al 2021] conducted a systematic review of the application of agile methods to embedded software development. They identified that XP and Scrum are the methods more used by these projects.…”
Section: Ronkainem and Abrahamssonmentioning
confidence: 99%
“…An embedded system is a combination of computer hardware and software that is intended to perform a particular function inside a larger system [1]. A wide range of embedded systems can be found in different applications, from digital watches and cameras to medical systems, autonomous systems, and avionics [2].…”
Section: Introductionmentioning
confidence: 99%